PENGEMBANGAN MEDIA LAYANAN INFORMASI BERBASIS WEB UNTUK MRNINGKATKAN DISIPLIN BELAJAR SISWA - Hidayat, Rian; Rosita, Tita; Septian, Reza (IKIP Siliwangi, 2024)
The lack of student learning discipline has an adverse impact on student outcomes and achievements in both academic and non-academic fields. If this is neglected, it will have a negative impact on his future. For this reason, it is necessary to have media that can improve student learning discipline, one of which is using web media. This research method uses research and development methods. While the subjects of the research were 8 class X students. Data collection uses observation, interviews, questionnaires and documentation. The results of the research show that 1) Web media development is carried out in accordance with research and development or RnD procedures. 2) The results of the validation show that the percentage obtained for material validation is 97.28%, while for material validation it is 89.38%. 3) There was an increase in the score of student learning discipline which previously obtained a score of 948 increased to 1247, with an increase in score of 299. Thus the researcher can conclude that web media can improve the learning discipline of class X students of SMA Al Bidayah Batujajar.